(untitled) (Palíndromo, 2026)
A una isla los llevaría… Estrategias de aparición de la subjetividad marica en la escena teatral chilena (I’d Take Them to an Island… Strategies for the Appearance of Queer Subjectivity in the Chilean Theatrical Scene), by Daniela Cápona, offers a critical reconstruction of six decades of theatre history from the perspective of sexual dissidence. Through a combination of theory, testimony, and archival material, the author rescues memories marginalized by official History and dismantles dominant narratives that have omitted or distorted queer presence. The “island” operates as an ambivalent metaphor: a space of pleasure and subversion, but also of confinement, torture, and disappearance, linking theatre to contexts of dictatorial repression, persecution, hiv/aids, and neoliberalism. The text spans from the adoption of international plays to the emergence of cabaret, brothel, and variety shows as strategies for visibility and resistance. Works and artists such as Ramón Griffero, Andrés Pérez, Hija de Perra, Blue Ballet, and El Gran Circo de Timoteo shape a map of artistic practices that politicize desire, reclaim humor as a tool, and frame the monstrous as a critical force. The aim of this book is to reconstruct genealogies of queer subjectivity in Chilean theatre, highlighting its aesthetic and political strategies in dialogue with the historical contexts that sought to erase them, in order to affirm its place in cultural memory and confront the gaps of official history.